OPTIMALISASI PENGEMBANGAN CREATIVE BRANDING EKOWISATA BOON PRING DI KABUPATEN MALANG - yulistiowati, irma mufita; Endayani, Fatmasari (Jurnal Komunikasi dan Kajian Media, 2023)
Creative tourism branding is an important process for carrying out attractive promotions of the identity of tourist attractions. The main goal is to attract tourists to come to this place. One of them is the Boon Pring educational tour in Malang Regency. In its development, Boon Pring ecotourism prioritizes conservation, social, economic, cultural, learning and education. Therefore, optimization is needed regarding the branding of the educational tourism destination Boon Pring, Malang Regency. This aims to increase the development of the tourism sector in Malang Regency. Data collection methods in preparing this research used observation and interviews. The results of this research are that tourism to Boon Pring creates creative destination branding by introducing the culture of the people around Boon Pring. Apart from that, to develop tourism branding, Pokdarwis collaborates with the community, local government and other stakeholders. They also create educational tour packages to attract visitors. Finally, to carry out creative branding, Pokdarwis also uses social media. However, promotional skills need to be improved so that the resulting content is more interesting. And consistency is also needed in carrying out promotions on social media.